Environmental Factors Contributing to Susceptibility to Tuberculosis - K. Lee, Kai; J. Milburn, Heather (Current Respiratory Medicine Reviews, 2013)
The environment can contribute to a person’s susceptibility to tuberculosis, with a number of factors increasing the risk of developing active disease. In this chapter, we shall examine the evidence for an association between TB and nutrition, smoking, alcohol, intestinal parasite infection, and the newer anti-TNF immunosuppressive drugs. For further in depth information, readers are guided towards reviews on individual topics where available. Concurrent disease, other immunosuppressive medication and HIV infection have been covered elsewhere.
Keywords: Alcohol